The Position of Living Law in Society as a Source of Criminal Law According to Law Number 1 of 2023 - Yosep Copertino Apaut (Jurnal Restorasi : Hukum dan Politik, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code marks a fundamental transformation of Indonesia's criminal law system through explicit recognition of living law as a source of criminal law. This normative juridical research analyzes the position of living law in the national legal hierarchy, its mechanism of application as a basis for punishment, and its implications for human rights protection and the principle of equality before the law. The research findings indicate that living law obtains normative legitimacy through Article 2 of the National Criminal Code with formalization mechanism through Regional Regulations requiring conformity with Pancasila values, human rights, and empirical validation. The transformation of the legality principle from formal to material reflects efforts to balance legal certainty with substantive justice in the context of Indonesian legal pluralism. Recognition of living law brings juridical implications including expansion of criminal law sources, changes in the role of judges in interpreting law, and potential differences in legal treatment across regions that must be safeguarded against discrimination. Implementation problems include tension between the dynamic characteristics of customary law and the static nature of regulations, complexity in determining territorial boundaries of application, and risks of bureaucratization that can eliminate the philosophical values of customary law. Improvements in implementing regulations, establishment of special supervisory bodies, and capacity building for law enforcement officers are needed to ensure proportional, just application of living law that respects citizens' constitutional rights.